Promotion of renewable energy sources: effects on innovation. (5th February 2007) - Ragwitz, Mario; Huber, Claus; Resch, Gustav
To meet existing and future targets for renewable energy sources, national governments, EU policymakers and electricity market stakeholders have a pronounced interest in designing optimal instruments for the promotion of Renewable Energy Sources in the Electricity sector (RES-E). This paper characterises the present status of the RES-E markets in Europe, the portfolio of promotional instruments currently applied across the EU and the progress the Member States have made in reaching the targets. In particular, existing support schemes are analysed in terms of their effectiveness in achieving additional RES-E generation and in terms of their ability to meet the targets at minimum costs (efficiency). Our empirical findings show that instruments which are effective also tend to be efficient. Further, the short- and long-term diffusion of specific RES technologies depends on the support schemes in place. Finally, the paper discusses the compatibility of different instruments to support RES-E in the context of more general energy policy objectives.